2015
DOI: 10.1002/jor.22819
|View full text |Cite
|
Sign up to set email alerts
|

Examination of survivin expression in 50 chordoma specimens—A histological and in vitro study

Abstract: Chordomas mainly arise along the axial skeleton and are characterized by their slow but destructive growth. Prognosis and quality of life are poor because treatment options are mainly limited to surgery and radiotherapy. Survivin, a member of the apoptosis inhibitor protein family, functions as a key regulator of mitosis and programmed cell death, and is overexpressed in many tumor types. The aim of this study was to determine the role of survivin in chordomas. Survivin expression was investigated in 50 chordo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(32 reference statements)
1
4
0
1
Order By: Relevance
“…Survivin is a member of the inhibitor of apoptosis protein family (IAP) and functionally suppresses the terminal effector enzymes caspase-3 and caspase-7 33, 34. Experimental findings have revealed inhibition of Survivin to prevent chordoma cell growth, and as expected, to induce apoptosis 35. Collectively, the decrease in Mcl-1 and Survivin reasonably explains how inhibition of CDK9 may induce apoptosis in chordoma cell lines.…”
Section: Discussionsupporting
confidence: 57%
“…Survivin is a member of the inhibitor of apoptosis protein family (IAP) and functionally suppresses the terminal effector enzymes caspase-3 and caspase-7 33, 34. Experimental findings have revealed inhibition of Survivin to prevent chordoma cell growth, and as expected, to induce apoptosis 35. Collectively, the decrease in Mcl-1 and Survivin reasonably explains how inhibition of CDK9 may induce apoptosis in chordoma cell lines.…”
Section: Discussionsupporting
confidence: 57%
“…Froehlich et al then explored the function of survivin in chordoma cells [ 79 ] and evaluated survivin expression in 50 chordoma cases (34 primary and 16 recurrent) from 44 patients using IHC. Twenty-three of 34 (68%) primary chordoma cases and 16 of 16 recurrent chordomas stained positive.…”
Section: Potential Future Treatmentsmentioning
confidence: 99%
“…The treatment reduced survivin protein expression and increased markers of apoptosis. Based on their findings, the authors suggested that YM155, which has been demonstrated to be safe in other diseases [ 80 82 ], could be a potential therapeutic agent for use in chordoma [ 79 ].…”
Section: Potential Future Treatmentsmentioning
confidence: 99%
“…Survivin belongs to the inhibitor of apoptosis (IAP) gene family and has an anti-apoptotic effect when it directly binds to caspase-3, a critical effector of apoptosis, which inhibits caspase-3 activation (33). It is important to note that survivin is also expressed in chordoma patient specimens and that the inhibition of survivin prevented chordoma cell growth (34). Moreover, the knockdown of survivin by RNAi reduced the clonogenic survival of human sarcoma cells (35).…”
Section: Discussionmentioning
confidence: 99%